2023
DOI: 10.1007/s11606-022-08002-5
|View full text |Cite
|
Sign up to set email alerts
|

Care Disruption During COVID-19: a National Survey of Hospital Leaders

Abstract: Background The COVID-19 pandemic caused massive disruption in usual care delivery patterns in hospitals across the USA, and highlighted long-standing inequities in health care delivery and outcomes. Its effect on hospital operations, and whether the magnitude of the effect differed for hospitals serving historically marginalized populations, is unknown. Objective To investigate the perspectives of hospital leaders on the effects of COVID-19 on their facilities’ operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…However, we found that outcomes were relatively stable across surge index strata for patients hospitalized during the pandemic for non–COVID-19 medical conditions. This finding is contrary to the commonly held belief, even in a survey of hospital administrators, that inpatients without COVID-19 received poorer quality of care and experienced worse outcomes during COVID-19 surges . Our findings suggest that the Canadian health care system may have, for the most part, weathered the storm during the pandemic or at least may have been used to running at near capacity even before the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…However, we found that outcomes were relatively stable across surge index strata for patients hospitalized during the pandemic for non–COVID-19 medical conditions. This finding is contrary to the commonly held belief, even in a survey of hospital administrators, that inpatients without COVID-19 received poorer quality of care and experienced worse outcomes during COVID-19 surges . Our findings suggest that the Canadian health care system may have, for the most part, weathered the storm during the pandemic or at least may have been used to running at near capacity even before the pandemic.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that care and prescribing patterns were also very similar after pandemic onset compared to the prior year in patients without ACSC also provides some reassurance that although earlier studies reported marked reductions in outpatient visits in the first few months of the pandemic 4,5 , this had largely recovered by the end of the first year, at least in our province. Our findings also call into question the commonly-held assumption expressed by two thirds of healthcare policy makers and administrators 14 and one third of elderly Americans 15 in recently published surveys that access to outpatient care for non-COVID conditions deteriorated after onset of the pandemic. Interestingly, we found that provider continuity actually improved for both those with or without ACSC during the pandemic, likely reflecting the fact that virtual care is easier to implement with patients already known to physicians rather than for new patients.…”
Section: Discussionmentioning
confidence: 55%
“…However, as we don't have any data on the content of each outpatient encounter, we are unable to address the question of whether quality and outcomes of outpatient care deteriorated after pandemic onset, two other concerns raised in the surveys of elderly Americans and healthcare administrators 14,15 . Further research is needed to investigate whether the shift towards virtual outpatient care has negatively impacted screening for and detection of new conditions (such as diabetes, atrial fibrillation, or cancer).…”
Section: Discussionmentioning
confidence: 99%
“…The true impact will depend on actual hospital performance and proportion of dual-eligible inpatient stays in FY 2026. Nonetheless, our analysis used the most recent performance data available before the COVID-19 pandemic, which resulted in the suspension of the HVBP program and other value-based payment programs . Second, our estimation of hospital-level HVBP payment adjustments relied on standardized operating amounts for hospitals designated as meaningful electronic health record users.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, our analysis used the most recent performance data available before the COVID-19 pandemic, which resulted in the suspension of the HVBP program and other value-based payment programs. 44 Second, our estimation of hospitallevel HVBP payment adjustments relied on standardized operating amounts for hospitals designated as meaningful electronic health record users. However, national data have shown that almost all acute care hospitals have achieved meaningful electronic health record use, with even higher rates among hospitals participating in the HVBP program.…”
Section: Limitationsmentioning
confidence: 99%